2011
DOI: 10.2350/10-09-0900-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Activated NOTCH2 is Overexpressed in Hepatoblastomas: An Immunohistochemical Study

Abstract: Hepatoblastoma is a pediatric malignancy characterized by the uncontrolled proliferation of immature hepatocytes (hepatoblasts). This disease is diagnosed primarily in children younger than 5 years and is disproportionately observed in former premature infants. Cytogenetically, hepatoblastoma is characterized by numerical aberrations, as well as unbalanced translocations involving the proximal region of chromosome 1q. The NOTCH2 gene has been mapped to this locus, and it is well established that the NOTCH gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…More impressively, inhibiting this pathway with cyclopamine induced a striking growth inhibition of hepatoblastoma cells (54). On the other hand, when analysing Notch signaling by immunohistochemistry, Litten et al revealed an overexpression of the NOTCH2 receptor in 92% of the tumors compared to normal liver tissues (55). This result corroborates the idea that hepatoblastoma arises from immature precursors as NOTCH2 is known to repress hepatoblast differentiation during embryogenesis and sees its expression decrease with liver maturation (56).…”
Section: Other Molecular Alterations Described In Hepatoblastomasupporting
confidence: 72%
“…More impressively, inhibiting this pathway with cyclopamine induced a striking growth inhibition of hepatoblastoma cells (54). On the other hand, when analysing Notch signaling by immunohistochemistry, Litten et al revealed an overexpression of the NOTCH2 receptor in 92% of the tumors compared to normal liver tissues (55). This result corroborates the idea that hepatoblastoma arises from immature precursors as NOTCH2 is known to repress hepatoblast differentiation during embryogenesis and sees its expression decrease with liver maturation (56).…”
Section: Other Molecular Alterations Described In Hepatoblastomasupporting
confidence: 72%
“…Accordingly, Notch signal pathway has been considered as a crucial regulator of EMT (Espinoza and Miele, 2013; Ishida et al , 2013; Yuan et al , 2014; Zoni et al , 2015). Furthermore, the overexpression level and oncogenic role of Notch2 have been observed in numerous human cancer types, such as lung adenocarcinoma (Mimae et al , 2012), glioma (Yu et al , 2015), cervical cancer (Zhang et al , 2014), hepatoblastoma (Litten et al , 2011) and salivary adenoid cystic carcinoma (Qu et al , 2016). We have revealed that protein level of Notch2 was upregulated in ESCC cancerous cancer and it could promote the proliferation and survival ability of EC 9706 and Eca 109 (Wang et al , 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of beta-catenin lead to nuclear translocation, activation of diverse genes, and increased cell proliferation. NOTCH2 overexpression has been recently reported in HB (Litten et al 2011 ). Lopez-Terrada et al ( 2009 ) investigated the canonical Wnt signaling pathway in HBs and correlated the histologic subtype, beta-catenin immunostaining, and mutation status of the CTNNB1 gene ( Fig.…”
Section: Hepatoblastomamentioning
confidence: 99%